Effects of death of a spouse on psychological well-being, attitude towards aging and social support - Desengano, Gretchen
This is a descriptive study aimed to determine the effects of death of a spouse on psychological well-being, attitude towards aging and social support in selected semi-mountainous barangays of Miag-ao., Eleven (11) males and fifteen (15) females aging 60 years old and below were chosen through purposive sampling as respondents. Psychological Well-Being Scale, Attitude Towards Aging Scale and Social Support Questionnaire were utilized to gather the necessary data. It was found out that widows in semi-mountainous barangays of Miag-ao Have an average level of psychological well-being. Generally, widowed persons held a negative attitude towards aging, manifested in their strong agreement to the negative stereotypes associated with older persons such as weak, senile and dependent on other people for their needs. In terms of social support, the findings are consistent with the previous researches that highlight the primary importance of family and relatives as sources of assistance, both in material and non-material aspects.